Super-late pulmonary recurrence after radical esophagectomy for esophageal squamous cell carcinoma. (2020) - Umemura, Akira; Akiyama, Yuji; Iwaya, Takeshi; Koeda, Keisuke; Sugimoto, Ryo; Sugai, Tamotsu; Endo, Fumitaka; Baba, Shigeaki; Nikai, Haruka; Nitta, Hiroyuki; Takahara, Takeshi; Otuska, Koki; et al.
Highlights: Super-late pulmonary recurrence of esophageal squamous cell carcinoma. Successfully resection and long survive after pulmonary metastasectomy. Surgical indication of pulmonary oligometastasis of esophageal cancer. Abstract: Introduction: Pulmonary metastases from esophageal squamous cell carcinoma (ESCC) are often detected bilateral and multiple lesions and are often accompanied by metastases to other sites. The concept of oligometastasis has been developed, and limited distant metastases have been considered as indications for surgical resection for the purpose of extending overall survival. We herein present a long-surviving case of super-late pulmonary recurrence of ESCC, seven years after radical esophagectomy. Presentation of case: A 71-year-old woman who underwent radical subtotal esophagectomy with three-field lymph node dissection with a diagnosis of an advanced poorly differentiated ESCC with cT3N1M0 seven years ago visited our hospital. Chest X-ray and computed tomography at the 7-year follow-up revealed a solitary pulmonary tumor, 1.5 cm in diameter, at the right middle lobe without any extrapulmonary metastases; however, we could not diagnose whether primary lung cancer or pulmonary metastasis of ESCC was present. Therefore, we performed thoracoscopic partial resection of the right middle lobe. A histopathological examination including immunohistochemical staining revealed that the tumor was not derived from both alveolar epithelium and neuroendocrine cells and was diagnosed as pulmonary oligometastasis of ESCC. She has been followed for four years without re-recurrence. Conclusion: Pulmonary oligometastases of ESCC should be considered as surgical indications if the tumor is detected after a long disease-free interval without any extrapulmonary recurrences.